Early angiographic changes of intra-aneurysmal flow after flow-diverter stent treatment are not predictive of therapeutic success. Issue 6 (December 2016) - Labeyrie, Paul-Emile; Gory, Benjamin; Sadeh-Gonike, Udi; Huguet, Nazyed; Sivan-Hoffmann, Rotem; Riva, Roberto; Courthéoux, Patrick; Turjman, Francis
Background and purpose: Flow-diverter stents (FDS) are new devices for the endovascular treatment of intracranial aneurysms (IAs) promoting progressive aneurysmal thrombosis. To date, the delay of aneurysmal exclusion remains unclear. We evaluated the correlation between angiographic changes in the first 24 hours and 12-month occlusion in aneurysms treated with FDS. Methods: We retrospectively analyzed the intra-aneurysmal flow by evaluating the in-flow and out-flow delays on preoperative, immediate postoperative, 24-hour and 12-month follow-up angiography. Dichotomy of in-flow and out-flow within the aneurysm was considered as the time of contrast filling and time of contrast washing relatively to the parent artery. The delay times were compared and correlated with the therapeutic success of FDS at 12 months of follow-up. Results: Out of 14 treated IAs, in 13 consecutive patients, n  = 10 (71%) aneurysms showed complete occlusion at 12 months. Between immediate postoperative and 24-hour control, 10 aneurysms (71%) demonstrated in-flow modification, with eight increasing, two decreasing and four having no change. There were no statistical differences in therapeutic success in relation to the different flow-related profiles of intra-aneurysmal flux. Out-flow modifications were found in 11 aneurysms (79%) between immediate postoperative and 24-hour control, with five increasing, six decreasing and three having no change. Similar to the in-flow changes, there were no statistical differences in therapeutic success relative to the flow-related profiles. Conclusions: Early angiographic changes after FDS placement are very frequent, but are not correlated with the 12-month technical success of flow-diversion techniques.